Engagement Resources and Personal Pronouns: Mediation in the Translation of English-Malay Self-help Books - Phoebe Ian Yee Lim; Charity Chin Ai Lee (Jurnal Arbitrer, 2026)
This study examines how translators mediate Engagement resources when translating English self-help books into Malay, focusing on authorial positioning, dialogic stance, and the management of alternative viewpoints. Using Appraisal Theory, extended to include person deixis as an Engagement strategy, the research employs a qualitative approach to analyse three cognitive self-help books and their Malay translations to examine the distribution of Engagement resources, retention rates in translation, shift typology, person deixis patterns, and the factors motivating these strategies. A total of 245 textual segments containing critical points were identified as units of analysis. These units were manually coded and analysed for Engagement resources, with intra-rater reliability procedures to ensure consistency. Analysis reveals that translators maintain most Engagement resources at the category level with a modest shift towards monoglossic statements. Furthermore, substantial cultural mediation occurs through changes in person deixis. Translators systematically shift the second-person you to the first-person kita (inclusive ‘we’), reshaping interpersonal relationships from hierarchical to egalitarian positioning. This mitigates the direct and individualistic tone characteristic of the English self-help discourse, aligning with Malay preferences for a more inclusive and collective perspective. The study contributes theoretically by demonstrating the need for diverse approaches to highlight cultural mediation in translation analysis. Practically, the findings benefit three key groups: translators can refine their strategies for conveying persuasive language in culturally appropriate ways; publishers can provide better guidance to translators through detailed and genre-specific briefs that emphasize interpersonal positioning; and translation training programs can incorporate Appraisal Theory and person deixis as analytical frameworks into their curriculum, helping students develop systematic approaches to managing interpersonal resources in accordance with cultural norms.